2011
DOI: 10.2741/3735
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin induces apoptosis and impairs head and neck carcinomas EGFR/ErbB2 signaling

Abstract: The development of head and neck squamous cell carcinomas (HNSCCs) is a multistep process progressing from precancerous lesions to highly malignant tumors. A critical role in HNSCCs development and progression is played by EGFR family members including EGFR and ErbB2. The aim of this study was to investigate the effect of apigenin, a low molecular weight flavonoid contained in fruits and vegetables, on growth and survival and on EGFR/ErbB2 signaling in cell lines derived from HNSCCs of the tongue (CAL-27, SCC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 0 publications
1
59
1
Order By: Relevance
“…Moreover, in breast cancer cells, at high doses, apigenin resulted in an arrest of cell growth by inhibiting the activity of several kinases involved in the downstream signaling following EGFR activation [54]. In another study performed on HNSCC cells in vitro , apigenin treatment inhibited survival and induced apotosis by reducing ligand-induced phosphorylation of EGFR and ErbB2 and modulating their downstream signaling [55]. …”
Section: Polyphenols Target Signal Transduction Pathways Involved mentioning
confidence: 99%
“…Moreover, in breast cancer cells, at high doses, apigenin resulted in an arrest of cell growth by inhibiting the activity of several kinases involved in the downstream signaling following EGFR activation [54]. In another study performed on HNSCC cells in vitro , apigenin treatment inhibited survival and induced apotosis by reducing ligand-induced phosphorylation of EGFR and ErbB2 and modulating their downstream signaling [55]. …”
Section: Polyphenols Target Signal Transduction Pathways Involved mentioning
confidence: 99%
“…The optical density (OD) of the samples was determined at 540 nm using a spectrophotometric plate reader (Wallac 1420 Victor; Perkin Elmer Inc., Waltham, MA, USA). The percentage survival of the cultures treated with the aforementioned compounds was calculated by normalizing their OD values to those of the control cultures (31,32). The experiments were performed in triplicate and repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…Cell pellets were resuspended in 70% ethanol and incubated for 1 h at -20˚C. Cells were then washed twice with cold PBS, centrifuged at 300 x g for 10 min, incubated for 1 h in the dark with propidium iodide (Sigma-Aldrich) at a final concentration of 25 µg/ml in 0.1% citrate (Sigma-Aldrich) and 0.1% Triton X-100 (Sigma-Aldrich), and analyzed by flow cytometry using a FACSCalibur™ cytometer (BD Biosciences) with CellQuest Pro 5.2 software (BD Biosciences) (31,32).…”
Section: Fluorescence-activated Cell Sorting (Facs) Analysismentioning
confidence: 99%
“…Apigenin's ability to induce apoptosis has been shown in several cell lines derived from tongue SCC, such as SCC-25 cells (Chan et al, 2012;Maggioni et al, 2013), CAL-27, and SCC-15 cells (Masuelli et al, 2011). Chan et al (2012) showed that apigenin inhibited SCC-25 cell growth, reporting that apigenin induced a cell cycle arrest in the G 2 /M phase.…”
Section: Apigeninmentioning
confidence: 97%